Hyperinflation, Currency Board, and Bust: The Case of Argentina - Jutta Maute (Peter Lang International Academic Publishers, 2006)
This book focuses on «Convertibilidad», the latest Argentine experience of exchange rate based stabilisation, and aims at isolating the main causes for its tragic collapse in 2001-2002. The characteristics of Argentina's high and hyperinflation during the 1980s are analysed, and the theory of currency boards is expounded. The stabilisation tool, an institutionally highly credible currency board arrangement (CBA), though highly effective, could not be an optimal long-term solution, given the country's structural and trade characteristics. The analysis of the causes of the CBA's collapse yields a complex picture of interacting factors, among them invaliding ones that had created multiple vulnerabilities over years, and triggering ones that unfolded their worst potential in meeting such vulnerable conditions.
Keywords: 330